Multiple Fault Attack on PRESENT with a Hardware Trojan Implementation in FPGA - Breier, Jakub (2016)
Internet of Things connects lots of small constrained devices to the Internet. As in any other environment, communication security is important and cryptographic algorithms are one of many elements that we use in order to keep messages secure. It is necessary to use algorithms that do not require high computational power, lightweight ciphers are therefore an ideal candidate for this purpose. Since these devices work in various environments, it is necessary to test security of implementations of cryptographic algorithms. In this paper, we explore a possibility of attacking an ultralightweight cipher PRESENT by using a multiple fault attack. Utilizing the Differential Fault Analysis technique, we were able to recover the secret key with two faulty encryptions and an exhaustive search of 216 remaining key bits. Our attack aims at four nibbles in the penultimate round of the cipher, causing faulty output in all nibbles of the output. We also provide a practical attack scenario by exploiting Hardware Trojan (HT) technique for the proposed fault injection in a Xilinx Spartan-6 FPGA.